2020
DOI: 10.1177/1943387520980237
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of a Custom-Made Mouthguard Reinforced With Different Elastic Modulus Laminates During a Simulated Maxillofacial Trauma

Abstract: Background/Aims: There is a lack of data regarding the influence of different laminates for mouthguard reinforcement in the mechanical response during an impact in the orofacial region. The aim of this study was to verify the influence of the laminate framework on the stresses and strains of the anterior teeth and displacement of ethylene-vinyl acetate (EVA) custom-made mouthguards during a simulated impact. The null hypotheses was that the different laminates reinforcement would present the similar effect in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
13
1
1
Order By: Relevance
“…For the bone tissue, the stress concentration area was at the crestal level of the alveolar bone in the buccal side, regardless of the design or material used in the mouthguard. Some of the published finite element studies do show a different critical area in the maxilla bone [16]. This behavior can be justified with the presence or not of the periodontal ligament (PDL).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the bone tissue, the stress concentration area was at the crestal level of the alveolar bone in the buccal side, regardless of the design or material used in the mouthguard. Some of the published finite element studies do show a different critical area in the maxilla bone [16]. This behavior can be justified with the presence or not of the periodontal ligament (PDL).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this design variable, the experimental works of Westerman et al [14] and Takeda et al [15] indicate that the inclusion of one air layer in the mouthguard material improves the characteristic impact of mouthguards. At the same time, the numerical study of Tribst et al [16] reported some behavior differences. The authors reported that the material's elastic modulus inside the MG influenced the stress distribution on the buccal surface of enamel.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The positive effects of a mouthguard to prevent tooth injury have been already reported in the literature using three-dimensional [ 3 , 4 , 6 ] and bi-dimensional finite element analyses [ 16 , 30 ]. There is a consensus about the stress magnitude reduction for dentin, enamel [ 3 , 6 , 16 ], and bone tissue [ 3 , 4 , 7 ] at the impact momentum when the mouthguard is in position. This study’s simulation corroborates the previous literature, indicating a stress magnitude decrease associated with the use of the novel hybrid occlusal splint-sportguard (HGM).…”
Section: Discussionmentioning
confidence: 98%
“…During a traumatic contact sport impact, the most suitable material to be used in mouthguards to protect the orofacial structures should be the flexible polymers, which distribute the stress concentration [ 15 , 16 ]. Coincidentally, rigid occlusal stabilization splints are considered an ideal option, as compared to soft occlusal splints, for patients with bruxism.…”
Section: Introductionmentioning
confidence: 99%